Evolution, motivation, and the mating/parenting trade–off. Issue 1 (2nd January 2019) - Beall, Alec T.; Schaller, Mark
Abstract: An evolutionary perspective on motivation implies an inverse relation between two motivational systems – one that regulates mate acquisition and the other that regulates parental care-giving. Study 1 ( N = 2252) used correlational methods to test whether an inverse relation manifests at the level of chronic individual differences. Results revealed that short-term mating orientation (STMO) was inversely associated with a nurturant disposition toward children, but was positively associated with a protective disposition toward children. Studies 2 and 3 used experimental methods to test whether the inverse relation manifests at the level of temporary cognitive accessibility. Study 2 ( N = 92) revealed that women (but not men) reported lower levels of STMO following an experimental procedure designed to activate the parental care motivational system. Conversely, results from Study 3 ( n = 308) suggest that both men and women reported lower levels of tender emotional responses towards infants following an experimental procedure designed to activate the mate acquisition motivational system. Together, these results provide novel evidence bearing on the psychological manifestations of a mating/parenting trade-off, while also implicating additional variables that may affect the nature of these manifestations.